Evaluation of Proton MR Spectroscopy for the Study of the Tongue Tissue in Healthy Subjects and Patients With Tongue Squamous Cell Carcinoma: Preliminary Findings - Boussida, Salem; François, Yvener; Heintz, Adrien; Saidak, Zuzana; Dakpé, Stéphanie; Coutte, Alexandre; Chauffert, Bruno; Devauchelle, Bernard; Galmiche, Antoine; Testelin, Sylvie; Goudot, Patrick; Constans, Jean-Marc (Frontiers in Oral Health, 2022)
Purpose: To non-invasively assess spectroscopic and metabolic profiles of healthy tongue tissue, and in an exploratory objective in non-treated and treated patients with tongue Squamous Cell Carcinoma (SCC). Methods: Fourteen healthy subjects (HS), one non-treated SCC (NT-SCC) and two treated SCC (T-SCC) tongue patients underwent Magnetic Resonance Imaging (MRI) and Single-Voxel 1H-MRS evaluations (3T and 1.5T). Multi-Echo-Times 1H-MRS was performed at the medial superior part (MSP) and the anterior inferior part (AIP) of the tongue in HS, while 1H-MRS voxel was placed at the most aggressive part of the tumor for tongue SCC patients. 1H-MRS data analysis yielded spectroscopic metabolites ratios quantified to total-Creatine. Results: In HS, compared to MSP, AIP1H-MRS spectra, revealed hhigher levels of Creatine, a more prominent and well-identified TMA-Cho peak. However, larger prominent lipid peaks were better differentiated in the tongue MSP. Compared to HS, the NT-SCC patient exhibited very high levels of lipids and relatively higher values of TMA-Cho peak. Interestingly, T-SCC patients showed almost no-proliferation activity. However, high lipids levels were measured, although they were relatively lower than lipids levels measured in the NT-SCC patient. Conclusion: The present work demonstrated the potential use of in-vivo 1H-MRS to non-invasively assess spectroscopic and metabolic profiles of the healthy tongue tissue, in a spatial location-dependent manner. Preliminary results revealed differences between HS, NT-SCC and tongue-SCC patients, that should be confirmed with more patients. 1H-MRS could be included, in the future, to the arsenal of tools for treatment responses evaluation and non-invasive monitoring of tongue SCC patients.